SENSIBILIDADE DE AMENDOIM FORRAGEIRO (ARACHIS PINTOI CV. ALQUEIRE) A HERBICIDAS PÓS -EMERGENTES - Coppetti, Felipe E.; Maixner, Adriano R.; Andreazza, Tiago; Coppetti, Daniel E.; Vivian, Rafael; Sartori, Cesar O. (Salão do Conhecimento, 2013)
Resumo